1970
DOI: 10.1103/physrevlett.24.9
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation in Copper Alloys

Abstract: The long-slit geometry has been used to measure the angular correlation of annihilation radiation from copper alloys. The alloys 0.975 Cu-0.025 Al, 0.95 Cu-0.05 Al, and 0.77 Cu-0.23 Ni display "necks" in momentum space. In units of the copper Fermi-surface neck, the measured neck radii of 1.3, 1.5, and 0.8, respectively, are consistent with the assumption that the energy-momentum relation is unchanged upon alloying.Recent investigations 1 " 4 of annihilation radiation from oriented single crystals of copper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the light of the theory [16], we discuss the relation between the measured oscillation periods and the extremal points at the spacer [21]; and closed triangles give the calculated results from KKR-CPA [20]. An open inverted triangle is the neck diameter of pure Cu from the de Haas-van Alphen effect [22].…”
mentioning
confidence: 99%
“…In the light of the theory [16], we discuss the relation between the measured oscillation periods and the extremal points at the spacer [21]; and closed triangles give the calculated results from KKR-CPA [20]. An open inverted triangle is the neck diameter of pure Cu from the de Haas-van Alphen effect [22].…”
mentioning
confidence: 99%
“…Indeed, it has been proven that this is the typical case for random binary alloys, so the k-space description of the electronic states, on average, is valid and the Fermi surface of many of these systems is well defined. As we discuss later, even small necks and pockets of the pure-host-metal Fermi surface survive in alloying even for large concentrations of the solute and these features are identified in ACAR [8,9] as well as oscillatory magnetic coupling experiments [25][26][27]. Since for most of the binary alloys the Fermi surface is well defined across the whole range of concentrations, it is of great interest to see how the shape and connectivity of the Fermi surface change with concentration.…”
Section: The Alloy Fermi Surfacementioning
confidence: 94%
“…In figure 2 the calculated neck diameter as well as the one measured using ACAR [8,9] and the one predicted from the oscillatory magnetic coupling period for the (110) direction [27] are plotted as functions of the Ni concentration. The agreement between the three different sets of data is striking.…”
Section: The Cu 1−x Ni X Alloys' Fermi Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the data concerning the resolution of the present apparatus (Section 3.1), it is evident that a decrease of kNp below the one of pure Cu could have been easily detected. A possible explanation as to why Hasegawa et al [22] and Murray and McGervey [26] found that adding Ni t o Cu decreases kft, is the difficulty of deriving k, from I ( @ curves. Moreover, the two groups had poor vertical resolutions: 5.4 mrad and infinite in comparison, respectively.…”
Section: Cunimentioning
confidence: 97%